Technical swimsuit benefits: An examination to determine if technical swimsuits make collegiate swimmers significantly faster - Wylie, K. (Goucher College, 2018)
The purpose of this study was to determine if technical swimsuits provided a significant advantage over swimmers wearing a traditional team suit. The measurement included a timed 100-yard freestyle swim. Results showed that there was no significant advantage for swimmers wearing a technical suit. There was no statistically significant relationship between technical swimsuits and upperclassmen.